(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The motivation for introducing IFGs is due to The first definition and concept of Intuitionistic Fuzzy Graph (IFG) was introduced. Karunambigai analyzed the properties of minmax IFGs in Shannon and Atanassov defined intuitionistic fuzzy graphs using five types of Cartesian products. In this paper IFGs so defined are named. Some isomorphic properties on IFGs are discussed. et al., discussed the properties of isomorphism on fuzzy graphs and properties of isomorphism on strong fuzzy graphs in which motivated us to develop the same on IFGs and on strong IFGs. The main aim of this study is to build basic definitions of an IFG which will be useful for the researchers for their future study in IFGs. Since Atanassovis the pioneer of our study, the title of the paper is given so. For graph theoretical definitions and throughout this paper all the properties are analyzed for simple minmax IFG.